The relationship between sense of coherence, coping strategies and suicidal ideation among youths in Malaysia - Shobhanah, Ramesh; Nur Imanina Amani, Mustakim; Reshmika, Elangovan (2022)
Suicide is still the largest cause of death among youths, and suicidal ideation are relatively common in both normal and clinical populations. In order to find out how well one can deal with life stressors that could have affect their suicidal ide ation, this present study investigates the relationship between sense of coherence (SOC), coping strategies (CS) and suicidal ideation (SI) among youths in Malaysia. There was a total of 262 individuals that were recruited through the use of the purposive sampling method. The data were collected by using survey form, which included items from the the Qualtrics online Type text here Risk Assessment Suicidality Scale (RASS), Sense of Coherence Scale (SOC St13), and Brief COPE. The statistical analysis was done by using the atistical Package for the Social Sciences (SPSS). Results showed a negative correlation between SOC and SI. As for the correlation between coping skills (CS) and SI, there is negative correlation between problemfocused CS and social support with SI; the a re is a positive correlation between avoidance CS with SI. Meanwhile, in contrast to our hypothesis, there is a positive correlation between positive reframing with SI. In regard to SOC and CS, results revealed a positive correlation between SOC and the us e of problem focused, positive reframing as well as social support as CS. Conversely, there is a negative correlation between SOC and avoidance CS. The findings offer a deeper understanding of the rationale SOC and utilization of CS Keywords can be associated with SI.